ANALISIS BENTUK DAN FUNGSI DEIKSIS DALAM NOVEL TERUSLAH BODOH JANGAN PINTAR KARYA TERE LIYE: KAJIAN SEMANTIK - M. Afif Ardiansyah; Rani Jayanti (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze the forms and functions of deixis in the novel Teruslah Bodoh Jangan Pintar by Tere Liye from a semantic perspective. Deixis is a linguistic element whose meaning depends on the context of utterance, including the speaker's identity, time, and place. This study employs a qualitative descriptive approach, with data sources consisting of dialogic and narrative utterances containing deixis. Data were collected through text study, identified, and classified into deixis types, namely person, time, and place, and then analyzed descriptively to interpret their function in constructing the meaning of utterances, plot development, character depiction, and socio-cultural context in the novel. Based on the analysis of 30 deixis data, the findings show that person deixis is the most dominant, used to indicate narrative perspective and interpersonal relationships among characters, while time and place deixis play a crucial role in clarifying the chronology of events and the story setting. These results confirm that deixis not only serves a linguistic function but also contributes significantly to narrative meaning and social dynamics among characters. Thus, a semantic study of deixis in this novel provides deeper insight into how language constructs literary reality and character interaction.